An Experiment Study on Performance of New Alternatives in Room Air-conditioner - Li Tingxun; Lu Jian; He Dongcai; Liu Zhen (Zhileng xuebao)
New HFO refrigerants, R32 and their mixtures have been developed and interested by air conditioner industries for their low GWP. In this paper, R410A was chosen to compare the performance with its potential replacements R32 and R447A. The RAC capacity, energy efficiency and discharge temperature were tested while changing the compressor speed, outdoor temperature. It was found that both R32 and R447A had better efficiency than R410A. Moreover, R32 has largest cooling capacity and also highest discharge temperature, and R447A had potential advantages for high ambient temperatures and high compressor speed conditions.